Cleanliness and school truancy in Kampung Tengah, Gombak - Zamri, Zahid (2022)
Purpose: Based from the discussion between the AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences with the Head of Villagers of the seven villages in the Setapak's district, there were a number of essential issues that need to be catered in order to improve the living environment of the people within the villages. Amongst the issues were the problems of cleanliness and school truancy. As the instructor of the Ethics and Politics course together with its students, we had chosen these two issues as the problems that we wanted to address in helping the society. First we gathered the data by conducting interviews with the villagers. Then we came out with videos and reports to highlight the factors and challenges that lead to the issues; and suggestions to solve the problems. Based on the findings, as the first intervention, an educational-based programme called the Ruhul Muhsin (Good Soul) programme was conducted to educate the children of the villages about cleanliness and school truancy.